The Influence of Fluctuations and Product Characteristics on Consumer Purchasing Decisions at the Rantauprapat Simple Gold Shop - Muhammad Irham Nasution; Jeni Sukmal; Syafaruddin Munthe (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this research is to determine the influence of product fluctuations and characteristics on consumer purchasing decisions at a simple gold shop in Rantauprapat. This research uses quantitative methods and an associative causality approach. The data collection technique used is through observation and interviews. The sample in this research was 86 respondents or consumers. The sampling technique is simple random sampling. The data analysis technique uses statistical techniques/SPSS by carrying out validity and reliability tests then for questionnaires and multiple linear regression analysis with the T Test and F Test to prove the hypothesis. The research results show that there is an influence of fluctuations on purchasing decisions, there is an influence of product characteristics on consumer purchasing decisions. The influence of fluctuations and product characteristics is 16.80% and the remaining 83.20% is influenced by other factors and variables.